Determination of frequency of specified structural congenital anomalies and the pattern of determinants affecting congenital malformations in prenatally diagnosed fetal anomaly cases before 20 weeks - Sood, Nishi; Thakur, Manish (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Congenital anomalies accounts for 8-15% of perinatal deaths and 13-16% of neonatal deaths in India. The aim of this study was to determine frequency of specified structural congenital anomalies and the pattern of determinants affecting congenital malformations in prenatally diagnosed fetal anomaly cases before 20 weeks Methods: The present study was conducted at Kamla Nehru State Hospital for Mother and Child, Indira Gandhi Medical College, Shimla. During the study period, all pregnant women with prenatally diagnosed fetal anomaly before 20 weeks, reporting to the Department of OBG, were enrolled for this non-interventional prospective observational study. The observations were analysed on a statistical basis in structured data collection form. Results: Congenital malformations were significantly more common in the age groups of 20-30 years, of low socioeconomic status, vegetarians and who were non-compliant regarding folic acid intake. The majority of women bearing malformed foetuses came from areas at altitude of 500-2000 meters. 33.33% of foetuses had amniotic fluid abnormalities. 83.33% of the foetuses had a single malformation. Central nervous system was the most common system involved (61.90%) out of which neural tube defects (76.91%) were commonest. 11.9% malformations were of the gastrointestinal tract out of which majority (60%) were omphalocele. 4.76% of the total malformations were of the musculoskeletal system. 4.76% malformations involved the genito-urinary tract and 2.38% of the total malformations were of the cardiovascular system and craniofascial anomalies. Conclusions: Early detection of major malformation during pregnancy helps in reducing the high morbidity and mortality of neonates due to congenital malformations because of termination of pregnancy. The commonest system found to be affected was central nervous system followed by gastro-intestinal system. Food fortification with folates and vitamin B12 is the need of the hour.